How Induced is Induced Investment - Brems, Hans (The Review of Economics and Statistics, 1955)
i. The problem. In the mid-I954 forecasting discussion a strong reason for optimism was found in the fact that while late-I953 and earlyI954 sales were down and inventory up, there was no substantial reduction in planned investment in plant and equipment for I954. Here is a behavior pattern that has been studied very little. But the length of the time unit used in induced-investment planning is an extremely important aspect of business behavior, for it can be shown to be crucial for the stability of macro-economic equilibrium. To show this is the purpose of the present paper.